A revision of dragon millipedes III: the new genus Gigaxytes gen. nov., with the description of three new species (Diplopoda, Polydesmida, Paradoxosomatidae) - Srisonchai, Ruttapon; Enghoff, Henrik; Likhitrakarn, Natdanai; Panha, Somsak (European Journal of Taxonomy, 2018)
The ‘gigas’ group of dragon millipedes, formerly placed in the genus Desmoxytes Chamberlin, 1923, is revised and assigned to the new genus Gigaxytes gen. nov. Desmoxytes gigas Golovatch & Enghoff, 1994 is the type species of the new genus and is redescribed as G. gigas (Golovatch & Enghoff, 1994) gen. et comb nov. Three new species are described: G. fusca gen et sp. nov. from Thailand and Myanmar; G. parvoterga gen et sp. nov. and G. suratensis gen et sp. nov. from Thailand. All Gigaxytes species are endemic to small distribution areas in limestone habitats in South Thailand and South Myanmar. Illustrations of external morphological characters and an identification key to all known species are provided as well as a distribution map.